Deepfake Technology: Ethical Issues and Legal Gaps in Indonesian Cyber Law - Made Marshall Vira Deva; irfan venny rahmayanti; Intan Giri Anjani; Sutan Faiz Rasyid; Muharman lubis (Acceleration, Quantum, Information Technology and Algorithm Journal, 2026)
The rapid advancement of artificial intelligence (AI) has enabled the emergence of deepfake technology, which allows the manipulation of images, audio, and video to produce highly realistic yet fabricated content. In Indonesia, the proliferation of deepfakes poses significant ethical and legal challenges. This study examines the ethical implications of deepfake technology and identifies gaps in Indonesian cyber law, specifically within the Electronic Information and Transactions Law (UU ITE No. 11/2008 as amended by UU No. 19/2019 and UU No. 1/2024), the Pornography Law (UU No. 44/2008), and the Personal Data Protection Law (UU PDP No. 27/2022). Using a normative juridical research method with qualitative analysis of primary legal sources and secondary literature, this study finds that existing Indonesian legislation does not explicitly regulate deepfakes, creating a legal vacuum that leaves victims predominantly women without adequate legal protection. The findings highlight the urgent need for specific regulatory provisions addressing deepfake creation, distribution, and non-consensual intimate imagery (NCII). This paper concludes by proposing recommendations for legislative reform and ethical frameworks to guide both policymakers and technology users in Indonesia.